Implementasi Algoritma Shuffle Random dan Linear Congruent Method (LCM) pada Media Pembelajaran Pengenalan Icon Kota - Anwar Anwar; Fauziah Fauziah; Ratih Titi Komala Sari (KITA Institute, 2022)
The development of science and technology for electronic media that is used by everyone using a smartphone, for this smartphone device, early childhood only recognizes the existence of games on this device. There are many methods used in distance learning using smartphone devices. The purpose of this study is to design a learning application for children aged 7-12 years to recognize city icons in Indonesia by using the drag and drop method with the placement of controls on random questions. this game also applies the Shuffle Random algorithm and the Linear Congruent Method (LCM) algorithm for randomizing practice questions. The results of the study using LCM can generate random number values of 7,4,1,8,5,2,9,6,3,0,7 indicating the process of randomizing the questions on the city icon is appropriate and does not experience repetition, with the Shuffle Random method. randomization of questions on the city icon resulted in 3,7,5,8,1,6,4,2,10,9 were appropriate and did not experience repetition. The recommended algorithm in this study according to the characteristics of randomization of questions is LCM because the process is simpler, easier to understand and the time used is shorter and more efficient.